PEMBANGKITAN WARNA ANGKA TOKEK DENGAN METODE LINIER CONGRUEN METHOD (LCM) - Haruno Sajati; Dwi Nugraheny; Antok Hermawan (Compiler, 2016)
Color blindness is an abnormality in terms of seeing certain colors that occur as a result of demage to come cells (cone cells) in the retina of the eye, so that people with color blindness can be hard  to catch a certaincolor spectrum. People suffering from color blindness would have difficulty distinguishing certain shades can not even see certain colors. Developed by Dr. Ishihara test Shinobu Ishihara in 1917, until now the Ishihara test methods still be one of the main option in almost all countries to identify someone who had color blindess. In the figure gecko color generation system with linear method congruen method (lcm) described the components of software and hardwer that is required in the manufacture of  color generator application numbers congruen gecko with a linear congruen method (lcm). The determination of the initial value of the constant linear congruen method (lcm) into the determination of the color composition result generated randomly. System testing and completion of a questionnaire completed by Guttman and Likert scale. Diman on functional testing system results obtained with Guttman scale 100% yes that users can guess the number that appears on the color generation process. And the interface testing diselesaika with Likert scale with 85% strongly agree result the system has a 94% look attractive and easy to use system.